Acylation modification and/or guar gum conjugation enhanced functional properties of pea protein isolate. (August 2021) - Shen, Yanting; Li, Yonghui
Abstract: There has been an increasing demand for diverse and more functional plant-based protein ingredients for food uses. This study aims to improve the functional properties of pea protein isolate through acylation and/or conjugation with guar gum and investigate the physicochemical characteristics of the modified proteins. Acylated pea proteins were prepared by reacting with acetic anhydride (AA) or succinic anhydride (SA) at 0.3 or 0.6 g of AA or SA per g protein, respectively. Guar gum-pea protein conjugates were prepared by incubating the mixture at a mass ratio of 1:20 and 1:40 at 60 °C for 24 h, respectively. Acylated-guar gum-conjugated pea proteins were also prepared to investigate their synergistic effects. Both conjugated and acylated pea proteins showed significantly improved oil holding capacity of up to 2.20 ± 0.05 and 2.09 ± 0.03 g oil/g protein, respectively, compared to the unmodified protein (1.03 ± 0.02 g oil/g). The acylated pea protein also had greater water holding capacity of up to 7.01 ± 0.31 g water/g protein compared to the unmodified protein (3.57 ± 0.05 g water/g). Emulsion capacity and stability were improved up to 96–100% and 95–100%, respectively, for the modified proteins (e.g., 1:20 conj., SA0.3/0.6, AA 0.3/0.6 conj., SA 0.3/0.6 conj.). The suspensions prepared with 9% acetylated pea protein formed firm gels. Sequential acylation and conjugation of pea proteins demonstrated more beneficial and synergistic effects on the water holding capacity and emulsifying properties. However, the in vitro gastrointestinal digestibility of the modified pea proteins decreased compared to that of the control pea protein. Overall, the acylated and conjugated pea proteins possessed superior functional properties that could be used as novel food ingredients in meat alternative or beverage applications. Graphical abstract: Image 1 Highlights: Functionalities of pea protein are enhanced by conjugation and acylation. Both conjugated and acylated pea proteins had better oil holding capacity. Emulsion properties were significantly improved for the modified proteins. Sequential acetylated-conjugated pea protein had the best gelation property. The modification altered protein physicochemical characteristics.